The Relationship Between Economic Growth and CO2 Emissions in EU Countries: A Cointegration Analysis - Onofrei, Mihaela; Vatamanu, Anca Florentina; Cigu, Elena (Frontiers in Environmental Science, 2022)
This paper explores the dynamics of the relationship between economic growth and CO2 emissions in the 27 EU member states in a panel setting for the period 2000-2017. We use qualitative sequential methodology, involving empiric analysis that provides coherence and viability for our study, but also quantitative methods, including Dynamic Ordinary Least Squares (DOLS), unit root tests and cointegration techniques. The results suggest the existence of a long run cointegrating relationship between growth and CO2 emissions in EU countries and the DOLS method indicates a statistically significant effect of economic growth on CO2 emissions for both versions of estimators, revealing that on average, a 1% change in GDP leads to 0.072 change in CO2 emissions. The study also exhibits that higher income levels lead to increased demand for environmental protection and underline the need for designing environmental policies, capable to reduce emissions during periods of economic growth. Moreover, we find that the status of economic growth does not automatically diminish climate vulnerability in EU countries, only the correct type of growth does, thus being necessary that EU policymakers be aware of the energy cost pressure and to achieve economic growth in relationship with appropriate tools in terms of climate risk management.